FRAUD ON GOVERNMENT: REVIEWED FROM ORGANIZATIONAL ETHICAL CULTURE, LEADERSHIP STYLE, AND LOVE OF MONEY - Annisa Mutia Rama Fade; Yesi Mutia Basri; Devi Safitri (Universitas Airlangga, 2022)
Fraud is actions and acts against the law that usually occur in an organization. The purpose of this study was to see how the influence of organizational ethical culture, leadership style, and love of money on fraud in Pekanbaru City Government ASN. The population in this study is the State Civil Apparatus (ASN) at the Pekanbaru City Government, as many as 7417 people. This study uses quantitative methods. The sampling technique used purposive sampling, with the characteristics of ASN who have a position and have work experience in a position of at least 1 year.The data collection technique used a questionnaire by distributing it directly to the Pekanbaru City Government OPD and also sending a questionnaire via google form. There were 207 questionnaires analyzed. The results of data analysis using WarpPLS 7.0 show that organizational ethical culture and leadership style have a negative effect on cheating in Pekanbaru City Government ASN, while love of money has a positive effect on fraud in Pekanbaru City Government ASN. The results of this study have a contribution to the government in efforts to reduce and prevent fraud, especially in the government sector.